PEMERTAHANAN BAHASA BALI DALAM RANAH MEDIA SOSIAL INSTAGRAM - Made Reland Udayana Tangkas (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The Balinese language as a major regional language should always be considered in terms of its resilience to face the dynamics of the times that tend to erode cultural elements. The Balinese language has also experienced marginalization due to the orientation of the people who tend to prioritize foreign culture as the influence of the uncontrolled tourism world. Thus, foreign languages are more in demand by modern society today than Balinese. Attention to this phenomenon was born from observers and activists of the Balinese language who feel that the Balinese language should be preserved and maintained as a mother tongue. These observers began to raise the Balinese language in the realm of social media